The Economic impact of foreign aid on poverty - MATETE, Tinaye Rudolph (KDI School, 2018)
This research paper examines the economic impact of foreign aid on poverty for Sub-Saharan African countries. In this empirical analysis I have ascertained that foreign aid has an impact in reducing poverty in 42 Sub-Saharan African countries from 1980-2013. Panel estimation techniques and instrumental variables are used in order to control for country specific time varying effects and endogeneity. Based on the empirical analysis, I concluded that aid is effective in reducing poverty after controlling for macroeconomic variables. The findings are consistent on all poverty measures, the poverty gap, poverty depth, and poverty severity. Thus, sound macroeconomic policies and good institutional quality are also necessary factors in achieving sustainable poverty reduction strategies in recipient countries.
Thesis(Master) --KDI School:Master of Public Policy,2018